Design and Fabrication of Patient-Specific Implant for Maxillofacial Surgery Using Additive Manufacturing - Rakesh Koppunur; Kiran Kumar Dama; Uzwalkiran Rokkala; Balaji Thirupathi; N. V. S. S. Sagar; Bhiksha Gugulothu (Advances in Materials Science and Engineering)
Patient-specific implants are well known for fixing the fracture for bone repairs. However, the exact fixation of the fabricated implant to the patients is a challenging task. To overcome this problem, in the present study two kinds of designs are developed and fabricated. Based on the exact fitting to the patient’s oral system, the best design is selected to fabricate. Computed tomography (CT) scan data of the patient oral anatomy is converted into a 3D model using the DICOM Software “Slicer 3D.” The patient-specific maxillofacial implant is fabricated using fused filament fabrication (FFF) and direct metal laser sintering (DMLS) techniques. Before fabricating real time product, a prototype is fabricated at the initial stage using FFF. Later, stress distribution and displacement of the implant was investigated using a FEM simulation. The conclusion of the present work results are potential for FFF of patient-specific implants out of Ti-6Al-4V.